If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15c + -15 = 4c + 5 Reorder the terms: -15 + 15c = 4c + 5 Reorder the terms: -15 + 15c = 5 + 4c Solving -15 + 15c = 5 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. -15 + 15c + -4c = 5 + 4c + -4c Combine like terms: 15c + -4c = 11c -15 + 11c = 5 + 4c + -4c Combine like terms: 4c + -4c = 0 -15 + 11c = 5 + 0 -15 + 11c = 5 Add '15' to each side of the equation. -15 + 15 + 11c = 5 + 15 Combine like terms: -15 + 15 = 0 0 + 11c = 5 + 15 11c = 5 + 15 Combine like terms: 5 + 15 = 20 11c = 20 Divide each side by '11'. c = 1.818181818 Simplifying c = 1.818181818
| x^2-30x=-56 | | 67+c=-789 | | -4.6=3.4-2y | | (a+9)+7bi=9-6i | | 7Y+10=3Y-2 | | 1-x=15-3x | | 5y+4x=2 | | 3x+2x+x+12+2x/4=360 | | 27=v+15 | | 5v-4=-4v+8v | | -6.7-6X=-0.1 | | 12+x=4+2x | | 5x+40f(x)x=-5 | | 6x^2=12x-9 | | Cos(4x-10)=0 | | 7x-5y=-68 | | H=-5t^2+7t-4 | | 1x+4y=120 | | 1x+4y=11120 | | 2-2v=v+64 | | x-11=90 | | 3x+y-z=1 | | 0.9375=x+0.25(3) | | 6x-2y-z=-14 | | f(x)=13x+52 | | 2lgx=2 | | (n+5)(p-14)=1400 | | 6y+2z=a+3y | | 2x+3y+z=1 | | 6y+2z=a+3fory | | 0=-5x^3+25x^3-17x | | 4x+3y=330 |